Correlation study between increased fetal movement during the third trimester and neonatal outcome - Cuiqin Huang; Wei Han; Yajing Fan (BMC, 2019)
Abstract Background We aimed to analyze the correlation between increased fetal movements in the third trimester and neonatal outcomes. Methods We enrolled pregnant women (n = 219) who reported increased/excessive fetal movements in the third trimester in our hospital. A control group of healthy women (n = 278) who had undergone regular childbirth and delivery in our hospital during the same period and did not report abnormal fetal movements were also recruited. All pregnant women underwent fetal non-stress test. We analyzed the neonatal weight, appearance, pulse, grimace, activity, and respiration score, degrees of amniotic fluid contamination, amniotic fluid volume, conditions of umbilical cord around the neck and cord length, and incidence of small for gestational age. In addition, the incidence of preterm delivery, cesarean section rate, postpartum hemorrhage, and other postpartum complications were also analyzed. We then analyzed the correlation between increased/excessive fetal activity and neonatal outcomes. Results Women with complaints of increased/excessive fetal movements exhibited increased fetal movements mainly around 31 and 39 weeks of gestation. Several pregnancy variables, including number of previous delivery, gestational age (less than 34 weeks and more than 37 weeks) and vaginal birth rate, were associated with increased/excessive fetal movements. In addition, women who reported increased/excessive fetal movements had higher odds of large for gestational age (LGA), particularly those with gestational age over 37 weeks. Conclusion Increased/excessive fetal movements may be used to predict adverse neonatal outcome such as LGA.